MECHANICAL PROPERTIES OF LUNGS IN PATIENTS PROGRESSING MUSCULAR DYSTROPHY VARIOUS SEVERITY OF THE DISEASE - K. F. Tetenev; T. N. Bodrova; F. F. Tetenev (Бюллетень сибирской медицины)
Results of research of biomechanics of breathing at patients with progressing muscular dystrophy (PMD) and their interpretation are unique. Compared indicators of ventilating function of lungs and indicators of mechanics of breathing at 31 patients with PMD to 1–2 extent of motive frustration and 17 patients with 3–4 extent of motive frustration. In both groups of sick MVL and OFV-1 are lowered to the same extent, bronchial resistance isn’t increased. In the 2nd group the reserve volume of an expiratory is reduced for the account decrease in force of respiratory muscles is decreased. Elastic draft of lungs is reduced, the coefficient of functional activity of lungs is increased. At spontaneous breath the tensile properties of lungs are lowered, increased elastic fraction of work of breathing. The general nonelastic resistance of lungs is on the average equally increased in both groups at the expense of increase of tissue friction. At 12 sick PMD the abnormal respiratory loop came to light: completely I was absent at 8 patients and at 4 there was no inspiratory or expiratory part of a loop. Changes of indicators of mechanics of breath are the in generally functionally, and are considered as manifestation of compensatory strengthening of function of an intra pulmonary source of mechanical energy.